Effect of Vitamin B12 supplementation in late-life depression: A randomized controlled trial - Pooja Misal; Shrikant Srivastava; Akanksha Sonal; Vivek Agarwal; Wahid Ali (Journal of Geriatric Mental Health)
Background: Late-life depression (LLD) has a poor response to the first-line standard antidepressant medications. This study aims to determine the effect of Vitamin B12 supplementation as an augmentation to the antidepressant medications as the first-line therapy in LLD to accelerate and/or maximize the response and remission. Materials and Methods: It was a prospective randomized controlled trial of 4 weeks; 62 depressed older adults (age >50 years) with low but not below the normal range of serum Vitamin B12 levels (>187 but <350 pg/ml) were randomized to receive either Vitamin B12 (7500 μg intramuscular injection over 15 days in 5 divided dosages) and an antidepressant (case) or only an antidepressant (control). Structured assessment of depressive disorder was carried out on days 0, 14, and 28, using hamilton rating scale for depression (HAM-D) and Geriatric Depression Scale Hindi version (GDS-H). Hindi Mental Status Examination was used at baseline to exclude primary cognitive impairment. Results: There was a significant decline in the depression scores in the Vitamin B12 supplementation group on both the HAM-D (P = 0.01, partial η2 = 0.113) and GDS (P = 0.01, partial η2 = 0.102) between days 0 and 28, with statistically more remitted subjects in the supplementation group (78% vs. 47%, P = 0.001). Conclusion: Vitamin B12 supplementation to standard antidepressant significantly improved the response and remission rates in subjects with low-normal serum Vitamin B12 levels.